Influence of pontic design on speech with an anterior fixed dental prosthesis: A clinical study and finite element analysis. - Hu, Shanshan; Wan, Jia; Duan, Lunliang; Chen, Junyu (Journal of Prosthetic Dentistry, 2021)
Patients may experience disturbed articulation after treatment with a fixed dental prosthesis. However, studies that assess the relationship between fixed dental prosthesis design and the accuracy of speech sound production are lacking. The purpose of this clinical and finite element analysis (FEA) study was to examine the influence of pontic design on speech with anterior fixed dental prostheses. First, an articulation test was carried out in which a partially edentulous participant was required to pronounce 4 Chinese words containing the voiceless fricative/s/while wearing fixed dental prostheses with 2 types of pontic designs. The oral morphology was obtained by cone beam computed tomography (CBCT) scanning while the participant, wearing the 2 fixed dental prosthesis designs, was pronouncing the voiceless fricative/s/sound. The geometry of the oral cavity was then reconstructed by an image processing software program. Finally, a finite element model for sound wave propagation inside the oral cavity was developed within the framework of the finite element analysis software program. By using this model, the sound pressure level of the 2 types of pontic design was characterized and quantified under different fundamental frequencies (F 0). The data were analyzed with 1-way ANOVA (α=.05). The experimental articulation test reported that the pontic design of fixed dental prostheses affected the speech production of the/s/sound (P <.001). The numerical study reported that the sound pressure level values were different under various fundamental frequencies. In addition, the pontic design of fixed dental prostheses affected the sound pressure level values, and the differences varied significantly from 420 to 1300 Hz (P <.05); however, the differences were not significant between 120 and 420 Hz (P >.05). Moreover, further comparisons of low F 0 (120 to 500 Hz), medium F 0 (520 to 900 Hz), and high F 0 (920 to 1300 Hz) reported that the differences in the medium F 0 area were most obvious (P <.001 for maximum sound pressure level value and P =.001 for sound pressure level value at Point Q). Both the fixed dental prosthesis pontic design and the fundamental frequency could affect the sound field distribution.